DISTINCTIVE FEATURES OF MALAYSIAN SOCIETY MODERNIZATION - Khojiev Tunis Nurkosimovich (Journal Park Publishing, 2025)
In this article analyzes the historical features of modernization of Malaysia. Also covers the process of forming a model of the development of Malaysia and the factors influencing it.
Keywords: Modernization, «Vision 2020», the bumiputera, NEP, GDP, Malaysian Technology Development Corporation – MTDC, TNC.